2017
DOI: 10.3920/bm2016.0073
|View full text |Cite
|
Sign up to set email alerts
|

Novel bioactive from Lactobacillus brevis DSM17250 to stimulate the growth of Staphylococcus epidermidis: a pilot study

Abstract: Commensal skin microbiota plays an important role in both influencing the immune response of the skin and acting as a barrier against colonisation of potentially pathogenic microorganisms and overgrowth of opportunistic pathogens. Staphylococcus epidermidis is a key constituent of the normal microbiota on human skin. It balances the inflammatory response after skin injury and produces antimicrobial molecules that selectively inhibit skin pathogens. Here we describe Lactobacillus brevis DSM17250 that was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…On the other hand, the importance of the normal resident skin flora cannot be understated and the importance of a balanced microbiota. Some research has shown how topical products can have a positive selective effect on the skin microbiota, for example a small study in humans demonstrated that Lactobacillus brevis cell‐free extract promoted the growth of beneficial bacteria such as S. epidermidis in subjects with dry skin while another showed how under certain growth conditions a commensal strain of S. epidermidis can suppress the growth of C. acnes , thus raising its potential in the treatment of acne . Although the results from this study are promising, human clinical studies, evaluating the safety and efficacy of topically applied L. reuteri DSM 17938 after repeated applications will be critical for understanding its interaction with an effect on the skin microbiota and what are its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the importance of the normal resident skin flora cannot be understated and the importance of a balanced microbiota. Some research has shown how topical products can have a positive selective effect on the skin microbiota, for example a small study in humans demonstrated that Lactobacillus brevis cell‐free extract promoted the growth of beneficial bacteria such as S. epidermidis in subjects with dry skin while another showed how under certain growth conditions a commensal strain of S. epidermidis can suppress the growth of C. acnes , thus raising its potential in the treatment of acne . Although the results from this study are promising, human clinical studies, evaluating the safety and efficacy of topically applied L. reuteri DSM 17938 after repeated applications will be critical for understanding its interaction with an effect on the skin microbiota and what are its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics consists of individual beneficial microorganisms or combinations thereof (Gibson et al ., ). Probiotics can be either consumed or applied topically and have been shown to confer positive effects in a variety of areas of human health (Holz et al ., ). Natural probiotics have a long history of success in human gut health and have shown promise in treating inflammatory bowel disease, necrotizing enterocolitis, allergies, urogenital problems and skin imbalances (Nakatsuji et al ., ).…”
Section: Data‐driven Advances In Human Healthmentioning
confidence: 97%
“…Natural probiotics have a long history of success in human gut health and have shown promise in treating inflammatory bowel disease, necrotizing enterocolitis, allergies, urogenital problems and skin imbalances (Nakatsuji et al ., ). However, administration of probiotics does not necessary re‐establish the microbiota to ‘normal’ levels (Petschow et al ., ; Holz et al ., ). Currently, there is still a lack of understanding about the mode of action and collateral effects of probiotic treatment on human health.…”
Section: Data‐driven Advances In Human Healthmentioning
confidence: 97%
“…Indeed, it has been reported that L. brevis DSM17250 secrets a peptide that stimulates proliferation of S. epidermidis . As a result, L. brevis DSM17250 supplementation may have indirect antimicrobial effects on skin pathogens [43]. Other probiotic strains have been reported to inhibit P. acnes directly.…”
Section: Probiotics and Skin Healthmentioning
confidence: 99%